The Role of the Surabaya Special Class I Immigration Office in the Prevention of Illegal Indonesian Workers Based on Law No. 6 of 2011 - Aldi Ferdian Basari; Amirul Mustofa; Ulul Albab; Widyawati Widyawati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to describe and analyze: the role of the Surabaya Special Class I Immigration Office to prevent Illegal Indonesian Workers and what are the obstacles and efforts made. The research method to be used is qualitative descriptive. Data Collection Techniques include: Interviews, Observations, Documentation. The research informant is the Head of the Suarabaya Special Class I Immigration Office. The data analysis technique using interactive model analysis was developed by Miles et al., (2014), namely data condensation, data presentation, and conclusion drawn. The results of the study show that the Surabaya Special Class I Immigration Office has a role as a regulator carried out by providing understanding and socialization to the public about the dangers of illegal migrant workers who will not get legal certainty in their placement areas. As a regulator, immigration supervision of Indonesian citizens is carried out when applying for travel documents, either out or into Indonesian territory or being outside Indonesian territory. As a facilitator, providing Travel Documents of the Republic of Indonesia (DPRI) to every citizen who will travel abroad as long as there are no burdensome things. The obstacles faced are Indonesian Prospective Workers who still often forge documents, still often abuse Travel Documents, lack of awareness of Indonesian Prospective Workers in compliance with Immigration documents. Some of the efforts taken include regular Counseling and Education, Pre-Immigration Consultations. Strengthening Cooperation with Recognized and Licensed Official Placement Agents. Strict Monitoring and Supervision of activities related to immigration. Strict Law Enforcement on placement agencies or prospective migrant workers involved in non-procedural practices. Collaborate with relevant agencies such as the Ministry of Manpower, the police, and migrant worker protection agencies to exchange information and support comprehensive prevention efforts such as the Indonesian immigration security agency.